Progressive collapse of structures - Starossek, Uwe (Thomas Telford, 2009)
Sets out a practical, systematic framework to give engineers the tools they need to anticipate the risk of progressive collapse of structures and apply this knowledge to design and assessment procedures.
Keywords: Structural failures.; Structural dynamics.; Structural design.; elektronické knihy; electronic books